Transapical transcatheter aortic valve implantation: the front door approach captures the world - Stähli, Barbara E.; Altwegg, Lukas (Cardiovascular Diagnosis and Therapy, 2012)
Since the first-in-man procedure in 2002 transcatheter aortic valve implantation (TAVI) has emerged as a novel less invasive treatment option for high-risk patients with severe symptomatic aortic stenosis (1,2). Transcatheter aortic valve implantation has evolved impressively in recent years. The technique is feasible and safe, hemodynamic results after TAVI are excellent and its prognostic impact has been proven in several randomized clinical trials (3-5). Conceptually, two different approaches are applied: the “front door” and the “back door” approach, namely implantation by transapical - “front door” - access or by retrograde - “back door” - access via the arterial system including transfemoral, axillary or subclavian access routes.